Reuse of dinar and dirham in the frame of contemporary Muamalah: A study in South Kalimantan, Indonesia - Hafizah, Yulia; Nilasari, Erissa; Iqbal Assyauqi, Moh. (Journal of Islamic Economics Lariba, 2024)
IntroductionThe Muslim community is making several efforts to reuse the dinar and dirham for transactions and other purposes in the current era.ObjectivesThis research examines the phenomenon of reusing dinar and dirham as alternative financial instruments in the South Kalimantan region. It aims to reveal the reasons behind the reuse of dinar and dirham and the form of activities carried out by the movement carried out by the contemporary Muslim community. MethodThis research method uses a qualitative approach with a case study on Komunitas Muamalah Kalsel, with data collection techniques through interviews, observations, and documentation studies.ResultsThe results show that the main reason for using dinar and dirham is theological, namely an effort to restore more authentic economic practices according to Islamic teachings, with legitimacy from local clerical figures. The results also reveal the existence of a unique alms distribution model through Pasar Muamalah, which exchanges fiat money into dirhams to be distributed to underprivileged communities. The results also identified three critical aspects of a faith-based financial system, namely (1) the stability of the intrinsic value of precious metals, (2) criticism of the fiat-based financial system that is prone to inflation, and (3) efforts to uphold the principle of economic justice in transactions.ImplicationsThe Muslim community can consider reusing dinar and dirham to maintain the religious and economic aspects of their daily transactions.Originality/Novelty This study contributes to better understanding of application of dinar and dirham in modern society.